Direct Evidence for the Modulation Caused by Ti Substitution of Ta in a (Ta2O5)0.92(TiO2)0.08 Ceramic by Analytical Electron Microscopy. Issue 2 (30th December 2013) - Wang, Xiaodong; Zuo, Jian‐Min; Hu, Hefei; Rong, Yonghua
Abstract : The high‐temperature tetragonal structure of Ta2 O5 was observed in a Ta2 O5 ceramic sample doped with 8 at.% TiO2 . Direct evidences for the modulation along [ 1 ¯ 10 ] direction caused by Ti replacing Ta are obtained based on atomic‐resolution high‐angle annular dark‐field lattice imaging and electron energy loss spectroscopy analysis. The atomic mechanism of Ti substitution of Ta is explicitly described based on the structure model along [110] direction projection.